Dietary Fads and Gut Mysteries Versus Nutrition with a Grain of Common Sense - Barry Mishkin; Seymour Mishkin (Canadian Journal of Gastroenterology)
Although nutritional self-help literature is directed at the general public, which usually allows the authors to evade critical review by the medical and scientific community, both doctors and lay people need to read with discernment and educated scepticism when major health claims are made. Many published claims are based on misconceptions and questionable logic, and it is important to be aware of the inconsistencies and wrong conclusions commonly found in dietary fads. Patients' questions and dietary practices over the past few years have helped the present authors become familiar with certain food fads and nutrition 'self-help' books, and develop responses to popular gut topics such as food allergies, food combinations and commercial food supplements. The authors also discuss whether fads can deliver on their promises and what to tell patients.